2020
DOI: 10.1186/s12879-020-05193-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasive non-typeable Haemophilus influenzae infection due to endometritis associated with adenomyosis

Abstract: Background: The widespread administration of the Haemophilus influenzae type b vaccine has led to the predominance of non-typable H. influenzae (NTHi). However, the occurrence of invasive NTHi infection based on gynecologic diseases is still rare. Case presentation: A 51-year-old Japanese woman with a history of adenomyoma presented with fever. Blood cultures and a vaginal discharge culture were positive with NTHi. With the high uptake in the uterus with 67 Ga scintigraphy, she was diagnosed with invasive NTHi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recent study from Japan demonstrated uterine infection with a prevalence of 2.0% in women with focal adenomyosis and 10.9% in women with diffuse adenomyosis 20 . The association between Haemophilus influenzae infection and CE associated with adenomyosis has been reported elsewhere 44 . All these scant information may support a possible role of uterine infection in the occurrence of CE in women with adenomyosis similar to endometriosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study from Japan demonstrated uterine infection with a prevalence of 2.0% in women with focal adenomyosis and 10.9% in women with diffuse adenomyosis 20 . The association between Haemophilus influenzae infection and CE associated with adenomyosis has been reported elsewhere 44 . All these scant information may support a possible role of uterine infection in the occurrence of CE in women with adenomyosis similar to endometriosis.…”
Section: Discussionmentioning
confidence: 95%
“…20 The association between Haemophilus influenzae infection and CE associated with adenomyosis has been reported elsewhere. 44 All these scant information may support a possible role of uterine infection in the occurrence of CE in women with adenomyosis similar to endometriosis. Future prospective studies on intrauterine infection in women with adenomyosis are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate was subsequently found to have the ftsI mutations, producing PBP3 amino acid substitutions (S357N, M377I, S385T, L389F, A502T and N526K). Nishimura et al reported a Japanese non-typeable BLNAR HI causing bacteraemia, secondary to infection of a massive uterine adenomyoma with endometritis; the isolate returned an MIC of 1 mg l −1 to cefotaxime (susceptible; CLSI M100-S31, 2021 methodology), and the patient became afebrile after 7 days of ceftriaxone, despite source control not occurring for a further 10 days (ftsI sequencing was not performed) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, discrepancies in susceptibility reporting for third-generation cephalosporins between the two of the most common AST methodologies [4,5] used by laboratories have major implications for population-level empirical treatment of life-threatening infections, as well as individual patient care. We have previously demonstrated how EUCAST Version 12 and CLSI methodologies give clinically relevant, discrepant results for classifying isolates of HI as beta-lactamase negative, ampicillin-resistant (BLNAR) [6]; although BLNAR detection has major implications for aminopenicillin and amoxicillin-clavulanic acid prescribing, it is increasingly recognized to be a signal for risk of resistance to third-generation cephalosporins in Europe and Japan via acquisition of mutations within penicillin-binding-protein-3 (PBP3) [7][8][9][10][11][12][13]. Nevertheless, implementing the EUCAST methodology means that a clinician would be more likely to change antibiotics to a more restricted agent (e.g.…”
Section: Introductionmentioning
confidence: 99%